The prevalence of edentulism and their related factors in Indonesia, 2014/15 - Supa Pengpid; Karl Peltzer (BMC, 2018)
Abstract Background Little information exists about the loss of all one's teeth (edentulism) among older adults in Indonesia. The aim of this study was to investigate the prevalence of edentulism and associated factors among older adults in Indonesia. Method This study examines the self-reported prevalence of edentulism and associated factors among older adults (50 years and older) in a cross-sectional national study using the Indonesia Family Life Survey IFLS-5, 2014/15. The community-based study uses a multi-stage stratified sampling design to interview and assess household members, with a household response rate of over 90%. Results The overall prevalence of edentulism was 7.2, 29.8% in 80 years and older and 11.8% in those with no formal education. In adjusted Poisson regression analysis, older age, living in five major island groups and having functional disability were associated with edentulism. In addition, among men, having quit and current tobacco use and among women, having low social capital were associated with edentulism. Further, in adjusted analysis, among men, edentulism was positively associated with hypertension and negatively associated with diabetes, and among women, edentulism was associated with functional disability. Conclusions Results suggest that overall and/or among men or women that older age, living in five major island groups, having functional disability, tobacco quitters and users and those with low social capital was associated with edentulism. The identified associated factors of edentulism may be utilized in oral health programmes targeting older adults in Indonesia.